Gardening Sebagai Media Edukasi Untuk Meningkatkan Kemampuan Motorik Anak: Gardening as an Educational Media to Improve Children's Motor Ability - Asyari, Asyari; Abidin, Ratno (Pedagogia : Jurnal Pendidikan, 2019)
The purpose of this paper is to find out the gardening as an educational medium to improve children's motorbike in the garden of Wonorejo II Surabaya nursery. The research method used qualitative descriptive with the subject of the research of children assisted by as many as 20 children aged between 4-6 years. In the procedure for implement- ing educator gardening learning using two languages, namely English and Indonesian. The results of the study showed that children seemed to enjoy learning and educators. They learn to explain the environment and if something goes wrong with the children when mentioning plants, leaves and flowers, they are given sanctions by singing while being guided by tutors using English. Then gardening becomes one of the media for the introduction of the environment (ecoliterasy) giving an impact on children's habits in understanding the importance of protecting the environment.